Simultaneous HPTLC-UV quantification of colchicine and gloriosine alkaloids in the natural population of Gloriosa superba L., collected from Eastern Ghats of India for the identification of elite chemotypes. Issue 9 (14th June 2020) - Misra, Ankita; Kumar, Bhanu; Shukla, Pushpendra; Srivastava, Sharad
Abstract: Intra-specific chemical variability in the natural population of Gloriosa superba from Eastern Ghats (India) was recorded through validated HPTLC method and in vitro antiarthritic activity of elite chemotypes was evaluated. In total, 36 population(s) of G. superba were mapped and, collected from the phytogeography and densitometric quantification through validated HPTLC-UV method revealed a significant ( p > 0.05) difference in the metabolite content of germplasm(s). Colchicine and gloriosine content varied from 0.005 to 0.275% and 0.003 to 0.119%, maximum was recorded in NBG-34 (Tirupati, Andhra Pradesh) and NBG-70 (Panchgani hill, Maharashtra) respectively. On cluster analysis, six chemotypes were selected for in vitro antiarthritic activity, although activity was not significantly different. The elite chemotype with highest metabolite(s) content did not exhibit the highest biological activity and thus suggests the synergistic action of extract toward the pharmacological activity. The study promotes the use of G. superba in herbal formulation development as an adjuvant therapy in gouty arthritis and will aid in site-specific exploration of elite chemotype(s) with validated pharmacological action to meet out the medicinal and commercial demands. GRAPHICAL ABSTRACT: